COOPERATIVE LEARNING THROUGH WEBQUEST AS INTERNET-BASED ENGLISH LEARNING MEDIA - Madayani, Nany Soengkono (Pusat Pengembangan Bahasa IAIN Tulungagung, 2015)
In language learning, technology is an attractive media to the students, even more since e-learning concept was found. Along with the development of the information technology, teachers should build up the learning process to be more interesting. Many educational institutions use computers and internet as a part of language classroom. Computers provide students with access to large numbers of authentic learning resources. One of the resources is WebQuests. Using WebQuests give students the opportunity to be exposed to many resources while they are in the classroom. WebQuests can be used for several different instructional purposes in the classroom while helping students to acquire and transform knowledge. The WebQuest is designed to deal with dilemma about how to combine technology with effective learning into an integrated activity in class. It is about how students collaborate with their partners to solve problems in a topic. They are also taught to access information on the internet, and it is into a positive direction.